2019
DOI: 10.4314/jae.v23i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Graduate Youths Towards Agro-allied Skill Acquisition and Entrepreneurship Development Programme in Oyo State

Abstract: The paper investigated the agro-allied aspect of the Skill and Entrepreneurship Development (SAED) programme of the National Youth Service Corps in Oyo State. Specifically, the study examined the personal characteristics of the corps members, determined the attitude of the corps members to agro-allied activities of the SAED and identified challenges facing corps members in executing the agro-allied activities. Pre-tested questionnaire was used to elicit information from 100% of the SAED participants which gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Th is fi nding suggests that respondents were aware of the benefi ts of the programme, which yielded a favourable disposition towards the SAED programme. Adelakun et al (2019) noted that despite the positive disposition recorded, the programme is still not fulfi lling its stated objectives. By contrast, Ovwigho and Ifi e (2009) carried out a study which revealed that the majority of youths had a negative attitude towards agricultural programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th is fi nding suggests that respondents were aware of the benefi ts of the programme, which yielded a favourable disposition towards the SAED programme. Adelakun et al (2019) noted that despite the positive disposition recorded, the programme is still not fulfi lling its stated objectives. By contrast, Ovwigho and Ifi e (2009) carried out a study which revealed that the majority of youths had a negative attitude towards agricultural programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Th e study by Adelakun, Lawal, Oyegbami and Oyedokun (2019) was on the agro-allied aspect of the Skill And Entrepreneurship Development (SAED) programme of the NYSC programme in Oyo State, with focus on the personal characteristics of the corps members, attitude towards agro-allied activities and impending challenges. To further improve the position of graduate youths towards the agro-allied skill set of SAED, fi nancial assistance, supervision, monitoring and psychological motivation should be advanced upon by all concerned stakeholders during as well as aft er the youth service programme.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on youth in relation to agriculture including Ojebiyi et al (2015), Alao (2018), Jokotola et al (2019) and Adedapo et al (2019) whose works though similar, differ as they only assess the willingness and interest of university graduates and undergraduates to venture into agriculture. The uniqueness of this study is that it took into cognizance youth perceptions of agribusiness as it determines young would-be entrepreneur's likelihood to venture into agribusiness.…”
Section: Introductionmentioning
confidence: 99%